Desain LKS Berbasis Karakter Komunikasi Matematis dan Kemandirian dengan Pendekatan PMR - Nurhadijah; Sulis Janu Hartati; Lusiana Prastiwi (Universitas PGRI Adi Buana Surabaya, 2020)
This research is based on learning mathematics which is generally centered on teachers, who are considered able to make students understand the material provided. Whereas, in the implementation of curriculum 2013 students should play an active role in learning. The techniques used in this research are observations, interviews, polls, tests and documentation. The learning Model in this study uses a realistic mathematical learning approach. The purpose of this research is to design the LKS with a realistic mathematical approach that is capable of developing mathematical and self-reliance communication characters in students. The research instruments used are interview guidelines, observation guidelines, LKS, expert assessment sheets, teacher and student response polls. The results showed that the LKS developed were said to be worthy of use based on the 4.2 and 3.75 scores of material experts and media experts. As well as scores 26.3 and 75.97 of students and teachers who show interesting LKS. So it concludes that the LKS are worth using and attracting teachers and students ' attention.